2016
DOI: 10.1177/1971400916665385
|View full text |Cite
|
Sign up to set email alerts
|

Is size an essential criterion to define tumefactive plaque? MR features and clinical correlation in multiple sclerosis

Abstract: Tumefactive multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. It has recently been described as a rare subtype of multiple sclerosis (MS) characterised by the appearance of solitary or multiple space-occupying lesions associated with imaging characteristics mimicking neoplasm. Atypical features include plaque size >2 cm with mass effect, oedema, and/or ring enhancement on magnetic resonance (MR) images.This study is a retrospective review designed to evaluate the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
0
19
1
Order By: Relevance
“…TMS is defined as a large (>2 cm) lesion on radiologic imaging, which is often accompanied by edema and mass effect and shows ring enhancement. 1,7,8 However, a recent trial showed that lesions <2 cm may exhibit similar imaging characteristics, reflecting the ambiguity of the definition of TMS lesions. 8 So far, no large-scale epidemiological data is available on TDD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TMS is defined as a large (>2 cm) lesion on radiologic imaging, which is often accompanied by edema and mass effect and shows ring enhancement. 1,7,8 However, a recent trial showed that lesions <2 cm may exhibit similar imaging characteristics, reflecting the ambiguity of the definition of TMS lesions. 8 So far, no large-scale epidemiological data is available on TDD.…”
mentioning
confidence: 99%
“…1,7,8 However, a recent trial showed that lesions <2 cm may exhibit similar imaging characteristics, reflecting the ambiguity of the definition of TMS lesions. 8 So far, no large-scale epidemiological data is available on TDD. 1,7 In older trials, the incidence of TDD was estimated 0.3 cases per 100,000 population per year, and the prevalence 1-2 per 1000 cases of MS, [9][10][11] with a slight female predominance.…”
mentioning
confidence: 99%
“…7 TDLs are most frequently encountered in women, usually young to middle aged with an average disease onset at 37 years of age. 3 Symptoms depend on location and usually include focal neurological deficits, seizures and aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…Tumefactive demyelinating lesions (TDLs) are a locally aggressive form of demyelination usually manifesting as a solitary lesion greater than 2 cm in size that may mimic a neoplasm on imaging studies 1,2 and may pose a diagnostic challenge in patients without a pre-existing diagnosis of multiple sclerosis. 3 These lesions more commonly occur in women with an average age of 37 years. 4 However, they may occur at any age, including in children.…”
Section: Introductionmentioning
confidence: 99%
“…TMS can mimic the clinical and radiological features of a neoplasm, cerebral abscess, or inflammatory process and can be diagnostically challenging for clinicians. It is often misdiagnosed, and while neuroimaging may narrow the differential, a biopsy may be needed to make the definitive diagnosis [ 5 , 6 ]. TMS is characterized by well-demarcated hypointense lesions on computed tomography (CT) and is hyperdense on T2 and relatively hypodense on TI.…”
Section: Introductionmentioning
confidence: 99%